2023
DOI: 10.1111/liv.15793
|View full text |Cite
|
Sign up to set email alerts
|

HBV reactivation in HBsAg−/HBcAb+ rheumatoid arthritis patients receiving biologic/targeted synthetic DMARDs

Meng Hsuan Kuo,
Chih‐Wei Tseng,
Ping‐Hung Ko
et al.

Abstract: BackgroundRheumatoid arthritis (RA) patients seropositive for hepatitis B core antibody (HBcAb) and negative for hepatitis B surface antigen (HBsAg) are at risk of hepatitis B virus (HBV) reactivation when treated with biologic or targeted synthetic (b/ts) disease‐modifying antirheumatic drugs (DMARDs). The study aims to investigate the risk in this population.MethodsFrom January 2004 through December 2020, 1068 RA patients undergoing b/tsDMARDs therapy and 416 patients with HBsAg−/HBcAb+ were enrolled. Factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…It is difficult to draw a conclusion regarding the sexual effects on HBV reactivation. A recent study with 2845 person-years of follow-up identified factors associated with HBV reactivation in RA patients receiving biologic/targeted synthetic DMARDs, revealing no significant sex differences in the multivariate Cox-regression analysis [ 41 ]. Addressing this question necessitates a large-scale cohort study, incorporating an analysis adjusted for potential confounding factors.…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult to draw a conclusion regarding the sexual effects on HBV reactivation. A recent study with 2845 person-years of follow-up identified factors associated with HBV reactivation in RA patients receiving biologic/targeted synthetic DMARDs, revealing no significant sex differences in the multivariate Cox-regression analysis [ 41 ]. Addressing this question necessitates a large-scale cohort study, incorporating an analysis adjusted for potential confounding factors.…”
Section: Discussionmentioning
confidence: 99%